ANALISIS KETERPADUAN PASAR BERAS DI KABUPATEN MANOKWARI - Agatha Wahyu Widati; Dwidjono Hadi Darwanto; Masyhuri Masyhuri (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2011)
This research was aimed to investigate 1) rice marketing channel in ManokwariRegency; 2) marketing margin in Manokwari regency; and 3) market integration of rice in Manokwari regency. Primary and secondary data were collected in this research. Primary data were applied in analysis of rice marketing channel, and marketing margin, while secondary data of rice price for the period of 2004- 2010 were applied in analysis of market integration. Augmented Dickey Fuller (ADF), and regression method were implemented in analysis of this research. Result of the analysis show thatthere are nine rice marketing patterns or local rice marketing channels in Manokwari regency. The longest channel was involved three institutions such as village level rice millerlhuller, regency wholesaler and retailer which have the largest marketing margin too. Most farmer utilize the sixth rice marketing pattern on marketing channel, involving two intermediate middleman such as rice millerlhuller and regency retailer. The channel has low marketing margin which motivated farmer for producing rice due to largest share of price accepted by farmers. Analysis of rice market integration at Manokwari regency show that rice price at wholesale level is integrated with that at retaillevel.Penelitian ini bertujuan ootuk mengetahui 1). Jalur pemasaran beras produksi Kabupaten Manokwari; 2). Marjin pemasaran beras produksi Kabupaten Manokwari; dan 3). Tingkat keterpaduan pasar beras di Kabupaten Manokwari; Penelitian ini menggunakan data primer dan data sekunder. Data primer ootuk mengetahui saluran, dan margin pemasaran sedangkan data sekunder ootuk mengetahui keterpaduan pasar dengan menggunakan data harga beras tahoo 2004- 2010. Metode analisis yang digunakan adalah analisis Augmented Dickey Faller (ADF), dan analisis regresi. Hasil analisis menunjukan bahwa terdapat sembilan pola pemasaran atau saluran pemasaran beras produksi Kabupaten Manokwari. Saluran terpanjang melibatkan sebanyak tiga lembaga perantara yaitu penggilingan, pedagang penampoog kabupaten dan pengecer kabupaten. Saluran yang panjang ini mempooyai margin pemasaran yang terbesar pula. Petani paling banyak menggunakan pola pemasaran beras pads saluran pemasaran yang keenam, yang melibatkan dua pedagang perantara yaitu penggilingan dan pedagang pengecer kabupaten. Persentase margin dari seluruh saluran tergolong rendah, hal ini akan mendorong petani ootuk lebih memproduksi beras karena harga yang diterima oleh petani menguntungkan, ini dapat dilihat dari share harga yang diterima oleh petani yang relatif tinggi. Analisis keterpaduan pasar beras produksi Kabupaten Manokwari menunjukan bahwa terdapat integrasi seeara vertikal antara harga beras di tingkat eeeran dan harga beras di tingkat grosir.